1998
DOI: 10.1093/hmg/7.7.1091
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in the LIM-Homeodomain Gene, LMX1B, in Nail-Patella Syndrome

Abstract: Nail-patella syndrome (NPS) is an inherited developmental disorder most commonly involving maldevelopment of the fingernails, kneecaps and elbow joints. NPS exhibits wide variation in phenotypic expression within and among families with respect to these features. Other skeletal abnormalities such as hip dislocation and club foot have also been reported in some individuals with NPS. There is an association between NPS and renal disease, and between NPS and open-angle glaucoma (OAG), but it is not known whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 32 publications
4
136
2
Order By: Relevance
“…NPS is caused by heterozygous mutations in the gene encoding the LIM-homeodomain transcription factor LMX1B. 1,2 Studies in Lmx1b À/À mice have shown that Lmx1b plays a crucial role in dorso-ventral patterning of the limb, patterning of the skull, morphogenesis and function of the podocytes and the glomerular basement membrane (GBM), and development of the anterior segment of the eye. 3 -8 In the central nervous system, Lmx1b is involved in developing dopaminergic and serotonergic neurons of the hindbrain and the midbrain, and dorsal interneurons of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…NPS is caused by heterozygous mutations in the gene encoding the LIM-homeodomain transcription factor LMX1B. 1,2 Studies in Lmx1b À/À mice have shown that Lmx1b plays a crucial role in dorso-ventral patterning of the limb, patterning of the skull, morphogenesis and function of the podocytes and the glomerular basement membrane (GBM), and development of the anterior segment of the eye. 3 -8 In the central nervous system, Lmx1b is involved in developing dopaminergic and serotonergic neurons of the hindbrain and the midbrain, and dorsal interneurons of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In the kidney, Lmx1b is expressed in podocytes. Lmx1b protein has two zincbinding LIM domains at the amino terminus and a homeodomain in the middle.…”
Section: Lmx1bmentioning
confidence: 99%
“…The syndrome is inherited in an autosomal dominant manner and has been shown to result from mutations in the LIM-homeodomain encoding LMX1B gene. [3][4][5][6] The LMX1B transcription factor plays a role in defining the development of dorsal specific structures during limb development; 7 its role in other organs is unclear. Analysis of over 60 LMX1B mutations in NPS families supports the hypothesis that the syndrome results from haploinsufficiency due to loss of function mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of over 60 LMX1B mutations in NPS families supports the hypothesis that the syndrome results from haploinsufficiency due to loss of function mutation. [3][4][5][6] During the search for LMX1B mutations causing NPS, a 17bp deletion was identified upstream of the 3' splice consensus which removed a consensus branchpoint sequence. The effect of this deletion on the splicing of LMX1B RNA was studied further.…”
Section: Introductionmentioning
confidence: 99%